THE IN VITRO AND EX VIVO EFFECT OF PHYLLANTHUS NIRURI METHANOL EXTRACT ON HEPATIC GLUTATHIONE S-TRANSFERASE ACTIVITY IN STZ-INDUCED DIABETIC SPRAGUE DAWLEY RATS - Bashir, Moath Kahtan; Ismail, Sabariah; Q, Ma H; Abdullah, Nurul Huda; Hussin, Abas Haji (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The aim of this study was to investigate the in vitro and ex vivo (acute and sub-chronic doses) effect of Phyllanthus niruri methanol extract (PNME) on the activity of cytosolic glutathione S-transferase (GST) in streptozotocin (STZ)-induced diabetic young female Sprague Dawley (SD) rats. Methods: Young female SD rats were induced type I diabetes mellitus using STZ (60 mg/kg i.v.). The in vitro study was performed on cytosolic fraction of diabetic rat livers using PNME in concentrations of 0.01, 1 and 10 Âµg/ml. Meanwhile, ex vivo studies were performed on diabetic rats using PNME in doses of 500, 1000, 2000 and 5000 mg/kg p.o. for acute study (1 day) and 100, 500 and 2000 mg/kg/day p.o. for sub-chronic study (14 days). The GST activity in the cytosolic liver fraction was measured using spectrophotometric analysis. Results: The in vitro study showed that, there is no significant effect of the three concentrations of PNME versus control on GST activity in cytosolic fraction of diabetic young female SD rat livers, while for ex vivo study, there is a significant dose independent induction effect on GST enzyme activity at all doses used in acute study. Meanwhile, sub-chronic study showed significant dose-independent induction effect at doses 500 and 2000 mg/kg. Conclusion: This study suggests that Phyllanthus niruri may increase the clearance of drugs that are metabolized by GST enzyme in phase II metabolism when given concomitantly with this plant extract. Key words: Phyllanthus niruri, GST, diabetic rats, cytosolic liver fraction, phase II metabolismÂ 